Reoperations and mortality in 383 patients operated with parallel screws for Garden I-II femoral neck fractures with up to ten years follow-up. Issue 12 (December 2016) - Do, Le Nhat Duc; Kruke, Torbjørn Marstein; Foss, Olav A.; Basso, Trude
Abstract: Introduction: The objective of this study was to identify indications and predictors for subsequent surgeries in the same hip and to evaluate life expectancy following screw fixation of undisplaced femoral neck fractures (FNF). The study further aimed to determine the necessary follow-up time for future studies aiming to evaluate the treatment of such fractures. Materials and methods: This is a single-center retrospective cohort study with prospectively collected data including skeletally mature patients with undisplaced FNFs operated between 2005 and 2013. Gender, age at fracture, American Society of Anesthesiologists score, smoking status and excess use of alcohol were retrieved from electronical medical records. Further, complications leading to all consecutive reoperations were registered along with time from primary operation to all reoperations, type of procedure during subsequent surgeries and time of death. Results: 383 patients with a median (range) follow-up of 77 (23–125) months were identified. Within 1, 2 and 5 years from primary surgery, 8%, 17% and 21% respectively, had at least one subsequent surgery in the same hip. 10% of the patients underwent salvage arthroplasty, however, in long time survivors; conversion to arthroplasty was estimated in one out of four. Posterior tilt of the femoral head was a predictor for new surgeries due to instability of the bone-implant construct, but not for later avascular necrosis. For patients 70 years or older, the one-year mortality in men was 32% with an expected survival of approx. 2.5 years, compared to 17% and 5.5 years in women. Conclusions: Screw fixation of undisplaced femoral neck fractures appears to be a safe procedure in particular in the absence of a posterior tilt of the femoral head. Conversion to arthroplasty was estimated to occur in one out of four of long time survivors. Men have a particularly poor medical prognosis and should receive careful medical attention. In order to capture 80% of reoperations, clinical studies and register studies must have a follow-up time of at least two years.